Mengenang Munir Said Thalib: Komitmen Tanpa Batas untuk Penegakan HAM di Indonesia - George M. Ch A. D. Soge; Marianus Ronaldo Tiba; Yulianus Y.M Rudeng; Blasius Wege; Hilarius A Sawokupu (Program Studi Hukum Universitas Nusa Putra, 2024)
Discourse about human rights is a complicated issue that is often encountered in public spaces. The rise of human rights violations is the reason that humans can become a threat to each other. The historical context of the struggle for human rights enforcement in Indonesia, of course, can never be separated from the figure of Munir Said Talib. He dedicated his entire life to upholding human rights in Indonesia, even though it ended in tragic death due to poisoning. This article aims to comprehensively examine the traces of Munir Said Talib's struggle as an unlimited commitment to human rights justice in Indonesia. The methodology used in this paper is using library research methods. Based on the results of literature research and secondary data analysis, several important points were found: first, human rights are fundamental rights that every individual has, and are so integral to a person's existence that they cannot be revoked by themselves or others. Second, the discourse on human rights in Indonesia is still a crucial issue and remains relevant. Third, the discourse around human rights in Indonesia cannot be separated from the figure of human rights fighter Munir Said Thalib. Together with his colleagues and several institutions they formed, the traces of his struggle have become immortal and remain relevant. Even though he has died, his struggle remains.